Between-side differences in hand-grip strength across the age span: Findings from 2011–2014 NHANES and 2011 NIH Toolbox studies. Issue 6 (2nd November 2019) - Wang, Ying-Chih; Bohannon, Richard W.; Kapellusch, Jay; Washburn, Dana; Li, Xiaoyan; Yen, Sheng-Che; Rahman, Mohammad H.
ABSTRACT: This project was undertaken to describe percentage differences in the grip strength between the dominant and nondominant-sides of left- and right-handed males and females across the age span. Data used in the project were from population-based samples of participants: 13, 653 from the 2011–2014 National Health and Nutrition Examination Survey (NHANES) and 3, 571 from the 2011 normative phase of the National Institutes of Health (NIH) Toolbox project. Depending on how percentage differences were calculated, the overall grip strength was a mean 5.0–5.6% greater on the dominant than nondominant side. The percentage differences were significantly greater for individuals who were right-hand dominant rather than left-hand dominant. The differences also varied according to gender. We present summary data for percentage differences stratified by study, handedness, and gender. The values can be used to determine whether grip strength on one side is limited relative to the other.